1984
DOI: 10.1002/ddr.430040406
|View full text |Cite
|
Sign up to set email alerts
|

κ‐Agonist analogesics: Evidence for μ2 and δ opioid receptor antagonism

Abstract: Wood, P.L.: K Agonist analgesics: Evidence for p2 and 6 opioid receptor antagonism.Drug Dev. Res. 4:429-435, 1984.Despite a unique in vivo pharmacology, K agonists possess moderate to high affinities for p , 6, and K binding sites in vitro. By monitoring the antagonist activity of K agents on morphine-and DADLE-dependent changes in dopamine and acetylcholine metabolism we were able to demonstrate a specific p2 and 6 receptor antagonism for K analgesics. Furthermore, this antagonism was probably directly at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…On a similar line, Cover & Buckingham (23) showed that basal and surgical stress-induced HPA axis activity was enhanced by the x-opioid receptor antagonist MR-2266, suggesting that this receptor type mediates inhibitory inputs. The interaction of dynorphin, MR-2266 and MR-2034 with the u-opioid receptor (23,32,33) does not explain the findings of these studies, because this receptor mediates stimulatory inputs in most circumstances. In addition,…”
Section: Discussionmentioning
confidence: 80%
“…On a similar line, Cover & Buckingham (23) showed that basal and surgical stress-induced HPA axis activity was enhanced by the x-opioid receptor antagonist MR-2266, suggesting that this receptor type mediates inhibitory inputs. The interaction of dynorphin, MR-2266 and MR-2034 with the u-opioid receptor (23,32,33) does not explain the findings of these studies, because this receptor mediates stimulatory inputs in most circumstances. In addition,…”
Section: Discussionmentioning
confidence: 80%
“…125 There is disagreement on the effect of these decreases in muscle lipid on the organoleptic properties of muscle.126.127 The effect of intramuscular triacylglycerols on organoleptic properties could occur through replacement of firm muscle fibres by soft fat making the meat more tender; improved lubrication by the melted fat so that the meat appears more juicy; and the trapping and carrying of aroma compounds making the meat more tasty. 126 The effects of intramuscular fat content on tenderness appear to be sma1l 122 ,123 over the range of fat contents studied, although in older studies with intramuscular fat contents above 5% there were high correlations between marbling score and tenderness. 128-130 However, some more recent work reports correlations between tenderness and intramuscular fat content at levels up to 3% .127,131 The reasons for the reported differences are not clear since the pigs in most recent studies were of comparable age and other contributing factors such as low muscle pH were allowed for.…”
Section: Intramuscular Triacylglycerolsmentioning
confidence: 87%
“…Since there are relatively few kappa 1 opioid receptors that bind U50,488H in the rat brain, we chose to use dynorphin A 1-17 which has a higher affinity for the kappa 2 receptor subtype which is more abundant in rat brain (Zukin et al, 1988). However, since metabolites of dynorphin A 1-17 have been shown to have affinity for mu receptors (Garzon et al, 1983;Wood, 1984) it is possible that dynorphin A 1-17 -stimulated [ 35 S]GTP␥S binding may be a result of both kappa and mu receptor stimulation.…”
Section: Discussionmentioning
confidence: 99%